Transcriptome and DNA Methylome Dynamics during Triclosan-Induced Cardiomyocyte Differentiation Toxicity - Guizhen Du; Mingming Yu; Lingling Wang; Weiyue Hu; Ling Song; Chuncheng Lu; Xinru Wang (Stem Cells International)
Cardiac development is a dynamic process and sensitive to environmental chemicals. Triclosan is widely used as an antibacterial agent and reported to transport across the placenta and affect embryonic development. Here, we used human embryonic stem cell- (hESC-) derived cardiomyocytes (CMs) to determine the effects of TCS exposure on cardiac development. After TCS treatment, the differentiation process was significantly blocked and spontaneous beating rates of CMs were also decreased. Transcriptome analysis showed the dysregulation of genes involved in cardiogenesis, including GATA4 and TNNT2. Additionally, DNA methylation was also altered by TCS exposure, especially in those regions with GATA motif enrichment. These alterations of transcriptome and DNA methylation were all associated with signaling pathways integral to heart development. Our findings indicate that TCS exposure might cause cardiomyocyte differentiation toxicity and provide the new insights into how environmental factors regulate DNA methylation and gene expressions during heart development.